Effects of dim artificial light at night on locomotor activity, cardiovascular physiology, and circadian clock genes in a diurnal songbird. (1st August 2021) - Alaasam, Valentina J.; Liu, Xu; Niu, Ye; Habibian, Justine S.; Pieraut, Simon; Ferguson, Brad S.; Zhang, Yong; Ouyang, Jenny Q.
Abstract: Artificial light is transforming the nighttime environment and quickly becoming one of the most pervasive pollutants on earth. Across taxa, light entrains endogenous circadian clocks that function to synchronize behavioral and physiological rhythms with natural photoperiod. Artificial light at night (ALAN) disrupts these photoperiodic cues and has consequences for humans and wildlife including sleep disruption, physiological stress and increased risk of cardiovascular disease. However, the mechanisms underlying organismal responses to dim ALAN, resembling light pollution, remain elusive. Light pollution exists in the environment at lower levels (<5 lux) than tested in many laboratory studies that link ALAN to circadian rhythm disruption. Few studies have linked dim ALAN to both the upstream regulators of circadian rhythms and downstream behavioral and physiological consequences. We exposed zebra finches ( Taeniopygia gutatta) to dim ALAN (1.5 lux) and measured circadian expression of five pacemaker genes in central and peripheral tissues, plasma melatonin, locomotor activity, and biomarkers of cardiovascular health. ALAN caused an increase in nighttime activity and, for males, cardiac hypertrophy. Moreover, downstream effects were detectable after just short duration exposure (10 days) and at dim levels that mimic the intensity of environmental light pollution. However, ALAN did not affect circulating melatonin nor oscillations of circadian gene expression in the central clock (brain) or liver. These findings suggest that dim ALAN can alter behavior and physiology without strong shifts in the rhythmic expression of molecular circadian pacemakers. Approaches that focus on ecologically-relevant ALAN and link complex biological pathways are necessary to understand the mechanisms underlying vertebrate responses to light pollution. Graphical abstract: Image 1 Highlights: Zebra finches exposed to dim artificial light at night (ALAN, 1.5 lux) for 10 days. ALAN exposure increased nocturnal locomotor activity. Heart mass increased (cardiac hypertrophy) for males exposed to ALAN. No change in plasma melatonin or circadian gene expression in the brain or liver. Abstract : dim ALAN increases nighttime locomotor activity and cardiac hypertrophy but has no effect on rhythm of circadian clock gene expression or melatonin in zebra finches.